Length–weight and length–length relationships of Indo Pacific Champsodon nudivittis (Ogilby, 1895) in the Northeastern Mediterranean - Deniz Ergüden; Sibel Alagöz Ergüden; Deniz Ayas (Acta Aquatica: Aquatic Sciences Journal, 2026)
The Indo-Pacific gaper Champsodon nudivittis is a Lessepsian migrant species that has recently expanded its distribution in the eastern Mediterranean Sea. A total of 245 individuals (131 females and 114 males) were collected by commercial bottom trawling from depths of 42–70 m along the Mersin Bay coast between September and November 2023. The estimated b values indicated positive allometric growth in both sexes, suggesting favorable environmental conditions and successful establishment of the species in the study area. The length–length relationship between the three length measurements (TL-FL-SL) was highly correlated (r2>0.97, P<0.001). This research is the first reference on length-weight relationship, length-length relationships, and also a new maximum length (as 14.5 cm TL) from the Northeastern Mediterranean coast of Türkiye (Mersin Bay). The high number of collected individuals indicates that the species forms a resident population rather than representing occasional records. These findings provide baseline biological data for monitoring the spread and potential ecological effects of this non-native species in the northeastern Mediterranean ecosystem. Keywords: Champsodontidae; Gaper; Length; Mersin Bay; Parameters; Türkiye; Weight